2016
DOI: 10.1080/15384101.2016.1152435
|View full text |Cite
|
Sign up to set email alerts
|

Common pathway signature in lung and liver fibrosis

Abstract: Fibrosis, a progressive accumulation of extracellular matrix components, encompasses a wide spectrum of distinct organs, and accounts for an increasing burden of morbidity and mortality worldwide. Despite the tremendous clinical impact, the mechanisms governing the fibrotic process are not yet understood, and to date, no clinically reliable therapies for fibrosis have been discovered. Here we applied Regeneration Intelligence, a new bioinformatics software suite for qualitative analysis of intracellular signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…These HSC‐derived myofibroblasts are responsible for the increased secretion and deposition of matrix components such as collagen and basement membrane proteins (Friedman et al, ), which then act to modulate signalling networks in all of the other cell types resident within the fibrosing liver. Similarly, idiopathic pulmonary fibrosis is characterized by dysregulation of, among others, the TGF‐β, MAPK and PI3K/Akt signalling pathways (Makarev et al, ), leading to aberrant tissue repair and extensive ECM remodelling which leads to the clinical loss of lung function. The activation of these pathways, which occurs in both forms of fibrosis, will enhance cell survival and proliferation (Wells, ) and acts to hyper‐activate a pro‐fibrotic cellular phenotype thus perpetuating further ECM remodelling and changes in signalling networks.…”
Section: Dysregulation Of Ecm‐mediated Signalling Network In Diseasementioning
confidence: 99%
“…These HSC‐derived myofibroblasts are responsible for the increased secretion and deposition of matrix components such as collagen and basement membrane proteins (Friedman et al, ), which then act to modulate signalling networks in all of the other cell types resident within the fibrosing liver. Similarly, idiopathic pulmonary fibrosis is characterized by dysregulation of, among others, the TGF‐β, MAPK and PI3K/Akt signalling pathways (Makarev et al, ), leading to aberrant tissue repair and extensive ECM remodelling which leads to the clinical loss of lung function. The activation of these pathways, which occurs in both forms of fibrosis, will enhance cell survival and proliferation (Wells, ) and acts to hyper‐activate a pro‐fibrotic cellular phenotype thus perpetuating further ECM remodelling and changes in signalling networks.…”
Section: Dysregulation Of Ecm‐mediated Signalling Network In Diseasementioning
confidence: 99%
“…Platelet factor 4 (PF4) is identified as a marker for fibrosis, levels of which are elevated in patients with systemic sclerosis and correlated with the presence and progression of pulmonary arterial hypertension [7]. Studies have suggested that multiple fibrotic diseases are usually triggered by the same irritation and share a number of common pathways, such as transforming growth factor beta (TGF-β), interleukin-6 (IL-6), and integrin-linked kinase signaling [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Many of those genes were previously found to be fibrogenic, including those encoding NOX4, CTGF, PERIOSTIN, LOX, and CDH2. [15][16][17] Induction of NOX4, which encodes NADPH oxidase 4, is associated with the production of reactive oxygen species (ROS) and with several important signaling events, including LPS signaling and inflammasome activation. 18 These findings suggested that NOX4 plays an important role in the pathogenesis of myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%